RANCANG BANGUN BUCKET ELEVATOR PENGANGKAT GABAH - Suhendri, Ohen; ., Tamrin; Lanya, Budianto (The University of Lampung, 2014)
Farmers are generally included the grain into sacks manually way is to use the tub or bucket. It certainly require excessive manpower. An option to helping that activity by using mechanical handling devices such as bucket elevator. This research aims to design, manufacture and test of bucket elevators for handling of grain. The method used in this research is the design, manufacture and testing process. Design process is done using software autoCAD, which is followed by a manufacturing. The next process is the testing performed by two operators and three variation rotation. After doing the design and manufacture, it produced a bucket elevator with chain tilt angel 60º, 76,3 cm length, 74,15 cm width and 146 cm high. From the test results, obtained volume of bucket 0.410 liter/bucket. Capacity bucket elevator reach 20 kg/min, 16 kg/min and 14 kg/min at 54 rpm, 39 rpm and 45 rpm rotation sprocket. The highest capacity 20 kg/min achieved at 5 inch diameter pulley, with 54 rpm rotation sprocket. Keywords: Design, grain, bucket elevator, volume bucket, capacity bucket elevator.